Outcomes of Geriatric Trauma Patients on Preinjury Anticoagulation: A Multicenter Study. Issue 6 (June 2017) - Ang, Darwin; Kurek, Stan; Mckenney, Mark; Norwood, Scott; Kimbrell, Brian; Barquist, Erik; Liu, Huazhi; O'Dell, Annette; Ziglar, Michele; Hurst, James
Outpatient anticoagulation in the geriatric trauma patient is a challenging clinical problem. The aim of this study is to determine clinical outcomes associated with class of preinjury anticoagulants (PA) used by this population. This is a multicenter retrospective cohort study among four Level II trauma centers. A total of 1642 patients were evaluated; 684 patients were on anticoagulation and 958 patients were not. Patients on PA were compared with those who were not. Drug classes were divided into thromboxane A2 inhibitors, vitamin K factor-dependent inhibitors, antithrombin III activation, platelet P2Y12 inhibitors, and thrombin inhibitors. Multivariate regression was used to adjust for age, gender, race, mechanism of injury, and Injury Severity Score. No single or combination of anticoagulation agents had a significant association with mortality; however, there were positive trends toward increased mortality were noted for all antiplatelet groups involving thromboxane A2 inhibitors and platelet P2Y12 inhibitors classes. The likelihood of complications was significantly higher with platelet P2Y12 inhibitors adjusted odds ratio (aOR) 2.39 [95% confidence interval (CI) 1.32, 4.3]. The likelihood of blood transfusion was increased with vitamin K inhibitors aOR 2.89 (95% CI 1.3, 6.5), P2Y12 inhibitors aOR 2.76 (95% CI 1.12, 6.76), and combined thromboxane A2 and P2Y12 inhibitors aOR 2.89 (95% CI 1.13, 7.46). P2Y12 inhibitors were also more likely associated with traumatic brain injury aOR 2.16 (95% CI 1.01, 4.6). All classes of PA were associated with solid organ injury. There were no significant differences in the use of antiplatelet agents between patients with major indications for PA and those without major indications. Geriatric trauma patients on outpatient anticoagulants have a higher likelihood of developing complications, packed red blood cell transfusions, traumatic brain injury, and solid organ injury. Attention should be paid to patients on platelet P2Y12 inhibitors, vitamin K inhibitors, and thromboxane A2 inhibitor agents combined with platelet P2Y12 inhibitors. Opportunities exist to address the use of antiplatelet agents among patients without major indications to improve patient outcomes.